Inovasi Kolaboratif Dalam Meningkatkan Kesejahteraan Sosial Dan Ekonomi Di Banjar Amerta Sari, Kecamatan Ree, Kabupaten Sumbawa: Program Pkm Berbasis Ekonomi, Hukum, Pendidikan Dan Kebudayaan Hindu - Somiartha, Putu; Saridewi, Desak Putu; Sudarma, I Made; Pancawati, Ni Luh Putu Anom; Satya Widari, Ni Nyoman; Hery Juniawan, Ida Bagus; Habibi, mr; Timor Prajawati, Yanti; Mahadiwya Pradnya Paramita, Ni Made; Aji Dwi Sesa Putra, I Made (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2025)
This study aims to evaluate the impact of the Community Partnership Program (PKM) collaboration based on the economy, law, education, and Hindu culture in Banjar Amerta Sari, Ree District, Sumbawa Regency. Thru interviews, observations, and document studies, this research reveals that the PKM program has a positive impact on increasing community income thru Hindu culture-based entrepreneurship, agricultural technology training, and strengthening legal understanding and skills education. This program also strengthens the preservation of Hindu culture and enhances understanding of customary law as a channel for dispute resolution. The main challenges faced are limited access to technology and financial support for micro-enterprises, which hinders business development. This research concludes that multidisciplinary collaboration combining economics, law, education, and Hindu culture can be a sustainable solution for empowering rural communities and improving their quality of life.